2020
DOI: 10.5267/j.msl.2020.2.006
|View full text |Cite
|
Sign up to set email alerts
|

University students’ insight on brand equity

Abstract: The recognition of brand equity has been in a substantial amount of recent research. In this study, we investigated the indicators of brand equity, which include brand image, brand awareness, and brand loyalty, in the context of higher education in analyzing the students of 10 universities in Ho Chi Minh City, Vietnam. We collected a sample size of 340 people to conduct a path analysis using a Partial Least Square Structural Equation Modeling (PLS-SEM) approach. The results proved a significant relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
1
14
0
3
Order By: Relevance
“…Empirical findings have also proven the positive and significant effect of brand trust on brand loyalty (Dhurup et al, 2018;Gozukara & Colakoglu, 2016). Tran et al (2020) found a positive effect of brand trust on brand loyalty in the higher education sector. Customers will tend to repurchase or recommend a product or service to others when trust has been formed (Tran et al, 2020).…”
Section: Brand Trust In Brand Loyaltymentioning
confidence: 94%
See 1 more Smart Citation
“…Empirical findings have also proven the positive and significant effect of brand trust on brand loyalty (Dhurup et al, 2018;Gozukara & Colakoglu, 2016). Tran et al (2020) found a positive effect of brand trust on brand loyalty in the higher education sector. Customers will tend to repurchase or recommend a product or service to others when trust has been formed (Tran et al, 2020).…”
Section: Brand Trust In Brand Loyaltymentioning
confidence: 94%
“…Tran et al (2020) found a positive effect of brand trust on brand loyalty in the higher education sector. Customers will tend to repurchase or recommend a product or service to others when trust has been formed (Tran et al, 2020). Therefore, referring to the previous empirical findings, the fifth hypothesis proposed is: H5: Brand trust has a positive and significant effect on brand loyalty…”
Section: Brand Trust In Brand Loyaltymentioning
confidence: 94%
“…In addition, confidence and commitment should be linked, as trust in relation exchanges is essential; and the dedication to these valuable connections is also necessary (Nazet al,2020). Some observational findings have shown that brand belief has a major positive influence on brand interaction (Tran et al, 2020). Furthermore, brand trust was very necessary and a primary reason for the growth of brand loyalty (Tran et al, 2020).…”
Section: Brand Trustmentioning
confidence: 99%
“…Some observational findings have shown that brand belief has a major positive influence on brand interaction (Tran et al, 2020). Furthermore, brand trust was very necessary and a primary reason for the growth of brand loyalty (Tran et al, 2020).…”
Section: Brand Trustmentioning
confidence: 99%
“…Branding in higher education sector Researchers generally agree that one of the most important functions of the higher education marketing team is to build the institutional brand [6] and that the HE sector has much to gain from the benefits of successful branding [5,8,9]. In this case it is understandable, that HEIs ever so have been increasingly interested in developing their differentiated brands [10]. It is noticeable, that when searching for competitive advantages of the various educational institutions, the focus is shifted from the attributes of the product (for example product assortment or quality of the developed educational product) towards increasing the public authority and building of high brand loyalty.…”
mentioning
confidence: 99%